Porokeratotic Eccrine Ostial Dermal Duct Nevus: A Case Report of a Young Male With Disordered Keratinization - Mansi Agarwal; Shruti Sharma; Madhumitha Palanisamy; Paridhi Singh (Indian Journal of Dermatopathology and Diagnostic Dermatology)
Porokeratotic eccrine ostial and dermal ductal nevus (PEODDN) is a rare benign nevoid disorder of keratinization. It is considered as an epidermal nevus variant and is classified as an eccrine hamartoma, characterized by parakeratotic features. Here, we report a case of a young adolescent male with unilateral PEODDN.